2007
DOI: 10.1002/aoc.1265
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and spectroscopic characterization of dimethyl/di(n‐butyl)tin(IV)bis(O,O′‐ditolyl dithiophosphate) complexes. Crystal structures of Me2Sn[S2P(OC6H4Me‐o)2]2 and n‐Bu2Sn[S2P(OC6H4Me‐o)2]2

Abstract: The environment around the tin atom in both molecules may be described as having skew-trapezoid bipyramidal geometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…There is a considerable interest in tin(IV) derivatives of phosphorus dithioacids containing the S=P‐S‐Sn structural fragment due to their biological activity. S‐Triorganyltin dithiophosphate esters are used as bactericides, insecticides, fingicides, etc .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a considerable interest in tin(IV) derivatives of phosphorus dithioacids containing the S=P‐S‐Sn structural fragment due to their biological activity. S‐Triorganyltin dithiophosphate esters are used as bactericides, insecticides, fingicides, etc .…”
Section: Introductionmentioning
confidence: 99%
“…The review summarizes reported coordination compounds utilizing dithiophosphonates on the basis of 1,3,2,4‐dithiadiphosphetane‐2,4‐disulfides . The common methods of synthesizing S ‐organotindithiophosphates, dithiophosphinates and tetrathiophosphates were usually based on the reactions of the corresponding phosphorus dithioacids or their salts with organotin halides (also in the presence of β ‐diketones), oxides, hydroxides, tetraalkyltin or tributyltin isocyanates . We have recently developed alternative methods of synthesizing tin(IV) derivatives of phosphorus dithioacids by use tetraphosphorus decasulfide and 1,3,2,4‐dithiadiphosphetane‐2,4‐disulfides as dithiophosphorylating agents.…”
Section: Introductionmentioning
confidence: 99%
“…However, they have also depicted other bonding modes e.g. monodentate 14 , anisobidentate 15 and bridging 16 . Various dithiophosphate complexes finds broad applications in medicines 17 , as catalyst in asymmetric synthesis 18 , agriculture 19 , sol-gel processing 20 , anti-wear additive to gear and motor oils 21 , as heat stabilizers for polymers 22 , extraction 23 and analytical processes 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Dithiophosphate complexes of both transition and non-transition elements have received considerable interest due to their wide diversity in chemical [1]- [6] and biological systems [7] [8] O, O-Dialkyl and alkylene dithiophosphate ligands can coordinate to metal atoms in a monodentate or anisobidentate fashion [9] [10]. More recent applications of thio compounds are in the production of nanoparticles of metal sulfides [11] [12].…”
Section: Introductionmentioning
confidence: 99%